THE GENUS BURRETIODENDRON* Rehder (Tiliaceae) - AJGH Kostermans (REINWARDTIA, 1961)
Seven species of Burretwdendron are recognized,of which B.siamensis and B.yunnanensis are new to science.The distributional area of the genus covers Siam (one species), Yunnan (two species),Kweichow (one species);Kwangsi (three species)and Tonkin (two species).B. tonkinensis is reduced to the synonymy of B.hsienmu. A key to the species is presented.